Предмет: Алгебра,
автор: xlls
Разложите на множители:
1) a(2a + b)(a + b) − 4a(a + b)^2;
3) (2a + 3)(a + 5) + (a − 1)(a + 5);
5) (5m − n)^3(m + 8n)^2 − (5m − n)^2(m + 8n)^3
Ответы
Автор ответа:
1
Ответ:
=a*(a+b)*(2a+b-4) (выносим за скобки множ а и (a+b) в последних скобкахь- то, что осталось)
2) = 3m*(m-8)*(m+m-8)=3m*(m-8)*(2m-8)
3) =(a+5)*(2a+3+a-1)=(a+5)*(4a+2)=2(a+5)*(2a+1)
Похожие вопросы
Предмет: Математика,
автор: bognujen2
Предмет: Информатика,
автор: chpok180
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: itswasmeDio
Предмет: Алгебра,
автор: FILOSOF420